Conservation and preservation of textile: special reference to batik collection - Barkeshli, Mandana (Yayasan Budi Penyayang Malaysia, 2016)
Throughout human history, textiles have played a rich part in the lives and traditions of people of all cultures. They have been constructed using a wide variety of materials and techniques from natural fibers such as cotton, silk, flax, and wool to regenerated or manufactured fibers such as rayon, nylon, and polyester. Textiles need special care if they are to be preserved for the future. The basic textile components of a costume usually belong to one of three categories: protein (silk and wool), cellulose (cotton, linen, and ramie) and synthetic (viscose rayon, nylon, polyester, etc). Conservation is the profession devoted to the preservation of cultural property for the future. Conservation activities include examination, documentation, treatment, and preventive care, supported by research and education.